Microscopic, submicroscopic characterization of pro- and anti-inflammatory cell phenotypes of the lungs in conditions of experimental allergic inflammation - Popko, S. S.; Попко, Світлана Сергіївна (Запорізький державний медичний університет, 2022)
The aim is to study the microscopic and submicroscopic characteristics of pro- and anti-inflammatory cell phenotypes of the lungs under conditions of experimental allergic inflammation. Material and methods. We used histological and electron microscopic methods to study the lungs of 48 male guinea pigs in experimental ovalbumin-induced allergic inflammation, simulated by subcutaneous sensitization and subsequent intranasal inhalation with ovalbumin. Submicroscopic changes of respiratory endocrine cells, goblet cells, exocrine bronchiolar cells, mast cells, macrophages, eosinophils, endothelial cells of guinea pigs lungs were determined. Results. The most significant reactive submicroscopic changes were established on the 23rd and 30th days of observation in the form of an increase in the functional activity of exocrine bronchiolar and goblet cells, as evidenced by the presence of a light nucleus with a predominance of euchromatin, nucleoplasm of low electron-optical density, nucleoli, developed granular endoplasmic reticulum and an increase in the number of goblet cells secretory mucous granules by electron microscopic examination. The revealed ultramicroscopic features of respiratory endocrine cells (an increase in a number of “empty” core dense vesicles), eosinophilic granulocytes (piecemeal degranulation), an increase in the number of mast cells granules, numerous pseudopodia in macrophages are the confirmation of the active participation of these cell phenotypes in the initiation of inflammation during the early period of the allergic inflammatory process in lungs. Мета роботи – з’ясувати мікроскопічну, субмікроскопічну характеристику про- та антизапальних клітинних фенотипів легень в умовах експериментального алергічного запалення. Матеріали та методи. Застосувавши експериментальний, гістологічний та електронномікроскопічний методи, вивчили легені 48 самців морської свинки в умовах гострого овальбумін-індукованого алергічного запалення, яке моделювали шляхом підшкірної сенсибілізації та наступної інтраназальної інгаляції овальбуміном. Визначали субмікроскопічні зміни дихальних ендокриноцитів, келихоподібних і бронхіолярних екзокриноцитів, макрофагів, мастоцитів, еозинофілів та ендотеліоцитів судин гемомікроциркуляторного русла легень морських свинок. Результати. Найістотніші реактивні субмікроскопічні зміни виявили на 23 і 30 доби спостереження, а саме підвищення функціональної активності бронхіолярних і келихоподібних екзокриноцитів у складі епітелію дихальних шляхів. Про це свідчили наявність світлого ядра з переважанням еухроматину, нуклеоплазми низької електроннооптичної щільності, ядерця, розвинута гранулярна ендоплазматична сітка та збільшення кількості секреторних слизових гранул келихоподібних екзокриноцитів під час електронномікроскопічного дослідження. Визначили ультрамікроскопічні особливості дихальних ендокриноцитів: збільшення кількості «порожніх» везикул зі щільною серцевиною, еозинофільних гранулоцитів – ознаки часткової дегрануляції; збільшення кількості гранул високої електроннооптичної щільності в цитоплазмі мастоцитів; численні псевдоподії макрофагів є підтвердженням активної участі цих клітинних фенотипів в ініціації запалення протягом раннього періоду розвитку алергічного запального процесу в легенях.
Мікроскопічна, субмікроскопічна характеристика про- та антизапальних клітинних фенотипів легень в умовах експериментального алергічного запалення
Popko S. S. - ORCID ID: 0000-0002-5533-4556
Keywords: electron microscopy; exocrine bronchiolar cell; mast cell; respiratory endocrine cell; goblet cells; guinea pigs; електронна мікроскопія; бронхіолярний екзокриноцит; мастоцит; дихальний ендокриноцит; келихоподібний екзокриноцит; морська свинка